Re-design of Local Residence (Homestay) in Labuan Bajo as Tourism Area (NTT) based on Adjustment Characteristic of tourist to Manggarai Traditional Building - Laksono, Sigit Hadi (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2022)
Labuan bajo has several famous tourist such as: Komodo National Park, Lake Kelimutu, Batu Cermin, Kampung Bena, Seventeen Marine Park, Riung Island and Wae Rebo. With the increasing tourist sector in Labuan Bajo, more tourists come. With the increasing number of tourists, accommodation is also increasing and competing. The problem that becomes an issue here first is the existence of homestay residents who are less competitive with existing hotels and cottages. The second is the lack of character of traditional buildings displayed in homestay buildings, hotels, and cottages that already exist. So, this research aims to optimize homestays design to compete with other accommodation facilities. Based on the above problem issues, to solve the problem by analyzing, comparing, and evaluating the sample of tourist residences operating. The design method used is the Cyclical design Process method in order to get optimal design alternatives. The final result obtained is in the form of a draft proposal that includes the arrangement of the floor plan and the proposal of the appearance of the design that has been adapted to the traditional building character and the needs of tourists.